Structure and Transport Properties of Water and Hydrated Ions in Nano‐Confined Channels. Issue 6 (16th April 2019) - Zhu, Huajian; Wang, Yuying; Fan, Yiqun; Xu, Junbo; Yang, Chao
Abstract: Nano‐confined flow is ubiquitous in modern engineering and biomedical applications. As the peculiar phenomena of nano‐confined flow were continuously reported and traditional theories failed to describe them accurately, simulation efforts have been made to gain deeper insight. The objective of this paper is to provide an overview of the recent progress on nano‐confined flow, including water flow and hydrated ions transport. This report starts with the water behavior under nano‐confinement, summarizing the water structures, flow properties and their dependence on wall wettability, channel size, etc. The report also presents the efforts made to modify the existing theories to describe nano‐confined flows. Then, the report goes to the hydrated ions. The dehydration process of hydrated ions and ions sieving are discussed in detail, and the effects of membrane surface charge, grafting functional groups, and external field on ions transport are reviewed. In this Progress Report, the transport properties of water and hydrated ions in nano‐confined channels are highlighted, which is critical to the design and application of nanofluidic devices, such as nanofiltration membranes, biosensors, and other related fields. Abstract : Nano‐confined fluids are highly attracting interest due to the wide range of their potential applications. Here, the recent progress in simulation efforts and some theoretical works on both water and hydrated ions under nano‐confinement are summarized. In addition, the disparity with experimental results and some fundamental problems of simulations are highlighted.